Bantuan Hukum Sebagai Kewajiban Negara Untuk Memenuhi Hak Konstitusional Fakir Miskin - Ramdan, Ajie (Mahkamah Konstitusi Republik Indonesia, 2014)
Legal aid as the state’s obligation to fulfill the constitutional rights of the poor very interesting study. The provision of legal aid as the state’s obligation to fulfill the constitutional rights of the poor is to provide funding to legal aid through the state budget. Because the Law No. 16 Year 2011 on Legal Aid takes the concept of legal aid welfare model. This paper will analyze the decision of the Court No. 88/PUU-X/2011 the constitutional rights of the poor to obtain legal assistance that the duty of the state . The provision of legal aid as the state’s obligation to fulfill the constitutional rights of the poor expanded in the Law No. 16 Year 2011 on Legal Aid , involving not only advocate, but also paralegals, lecterur and college students of faculty of law. This is because the constitutional legal aid was adopted by Act No. 16 of 2011. Thus justice seekers who are unable or poor should get legal assistance in legal proceedings to obtain justice. Governments need to do the verification, selection, and evaluation, as well as provide accreditation for legal aid agencies that meet or do not qualify as legal aid.